Hepatoprotective Potentials of Menaquinone - 7 against Doxorubicin Associated Hepatotoxicity - Ruaa F. A. Al-Zubaidi (Journal of Global Pharma Technology, 2018)
Dox, is still widely used in modern cancer treatments for different type of malignancy despite the advent of targeted therapy. However, its beneficial effect was limited by its toxicity on various organs. The objective of this study was to investigate the hepatoprotective effect of menaquinone-7 against hepatotoxicity induced by doxorubicin in rats. Sixty adult rats of both sexes were used in this study; the animals were randomly enrolled into six groups of 10 animals each. Group I: negative control; Group II: Menaquinones-7 at a dose of 16µg/kg; Group III: Menaquinones-7 at a dose of 48µg/kg; Group IV: positive control (Doxorubicin 15mg/kg); Group V: Menaquinones-7 at a dose of 16µg/kg administered prior to a single dose of Doxorubicin 15 mg/kg; Group VI: Menaquinones-7 at a dose of 48 µg/kg administered prior to a single dose of Doxorubicin 15 mg/kg. On day twelve of the study, the liver of each animal was excised for homogenate preparation and estimation of malondialdehyde, total antioxidant capacity and caspase-3 by ELISA technique as the markers of oxidative stress and apoptosis respectively. High dose of Menaquinones-7 significantly (P<0.05) decreased malondialdehyde content, and increase total antioxidant capacity content in group VI compared to group IV. However, neither group V nor group VI exhibited significant (P>0.05) differences in caspase-3 activity in liver tissue homogenate compared to positive control group. Menaquinones-7 may have hepatoprotective effect against doxorubicin-associated hepatotoxicity in rats.Keywords: Menaquinone-7, Doxorubicin, Hepatotoxicity, Rats, Tissue homogenate.